2014
DOI: 10.2337/db14-1042
|View full text |Cite
|
Sign up to set email alerts
|

Niche-Dependent Regulations of Metabolic Balance in High-Fat Diet–Induced Diabetic Mice by Mesenchymal Stromal Cells

Abstract: Mesenchymal stromal cells (MSCs) have great potential to maintain glucose homeostasis and metabolic balance. Here, we demonstrate that in mice continuously fed with high-fat diet (HFD) that developed non-insulindependent diabetes, two episodes of systemic MSC transplantations effectively improve glucose tolerance and blood glucose homeostasis and reduce body weight through targeting pancreas and insulin-sensitive tissues and organs via site-specific mechanisms. MSCs support pancreatic islet growth by direct di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 47 publications
2
32
0
Order By: Relevance
“…Paracrine tissue support and immunomodulation by MSCs are imperative during acute tissue injury, and these occur in a tissue‐specific manner in vivo . Liver regeneration involves numerous tissue growth factors and cytokines .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paracrine tissue support and immunomodulation by MSCs are imperative during acute tissue injury, and these occur in a tissue‐specific manner in vivo . Liver regeneration involves numerous tissue growth factors and cytokines .…”
Section: Discussionmentioning
confidence: 99%
“…Paracrine tissue support and immunomodulation by MSCs are imperative during acute tissue injury, and these occur in a tissuespecific manner in vivo. 25,[57][58][59] Liver regeneration involves numerous tissue growth factors and cytokines. [48][49][50][51]60,61 HGF triggers hepatocyte proliferation and guides hepatic progenitor-cell differentiation into hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Although Chinese physicians are familiar with Chinese Diabetes Society guideline recommendations for the management of T2DM, evidence shows that many Chinese T2DM patients have poor glycemic control [6, 27, 28]. A possible reason for this is the overly cautious approach to insulin initiation and titration, which, in turn, is thought to be a result of physician anxiety about invoking events of hypoglycemia in patients.…”
Section: Discussionmentioning
confidence: 99%
“…In China, the impact of T2DM is particularly disconcerting: the Chinese T2DM population is nearing 100 million individuals—about a quarter of the global T2DM population—and is projected to reach 142.7 million by 2035 [3–5]. Moreover, recent data suggest that, in general, patients with T2DM in China have poor glycemic control; a large observational study conducted at 209 hospitals across China found that patients had a mean hemoglobin A1c (HbA1c) level of 9.6 ± 2.0 % before initiation of basal insulin [6], and it has been reported that only 35.9 % of Chinese T2DM patients who are treated exclusively with oral antidiabetic drugs (OADs) achieve HbA1c levels of <7 % [7]. …”
Section: Introductionmentioning
confidence: 99%
“…Currently in East Asia, patients with T2DM are commonly prescribed metformin/sulfonylurea, and the initiation of insulin therapy is often delayed [4, 5]. Because inadequately controlled T2DM can give rise to serious, irreversible medical complications, there is thus an urgent need to identify alternative treatment strategies that would improve glycemic control in the East Asian T2DM population.…”
Section: Introductionmentioning
confidence: 99%